2021
DOI: 10.3904/kjim.2019.421
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of gastric cancer in workers with occupational dust exposure

Abstract: Background/Aims: Workers who are exposed to dust in the workplace tend to show a higher incidence of gastric cancer. Nevertheless, scientific evidence to support an association between dust exposure and the risk of gastric cancer is inadequate. This study aimed to investigate whether or not occupational dust exposure influences the risk of gastric cancer. Methods: We collected the electronic data from the Pneumoconiosis Health Examination (PHE) program, provided by the Ministry of Employment and Labor and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…EAA is known to cause lung cancer and various respiratory system diseases, including pneumoconiosis [ 24 , 25 ]. Several studies have demonstrated that workers exposed to EAA have an increased risk of esophageal cancer, stomach cancer, and all GI cancers [ 18 , 26 , 27 , 28 , 29 , 30 ]. A previous study postulated that the lung clearance system can release inhaled EAA into the oral cavity, where they are constantly swallowed and enter the digestive tract [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…EAA is known to cause lung cancer and various respiratory system diseases, including pneumoconiosis [ 24 , 25 ]. Several studies have demonstrated that workers exposed to EAA have an increased risk of esophageal cancer, stomach cancer, and all GI cancers [ 18 , 26 , 27 , 28 , 29 , 30 ]. A previous study postulated that the lung clearance system can release inhaled EAA into the oral cavity, where they are constantly swallowed and enter the digestive tract [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The development of malignancy tumors are complex multistep processes attributed by many risks. It is widely known that dust particles of such pollution are related to cancer of many organs 24 , 25 . The pollutant elemental dust composed of the concentrations of heavy metals such as lead, zinc, nickel, copper, cadmium and chromium 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the size of pollutant particles is related to their ability to penetrate the respiratory system [1,20]. The inhalation of dust particles poses a significant issue because they cannot be exhaled or even cleared from the respiratory tract.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the nature of mining and quarrying activities, every source has the potential to emit particulate matter [20]. Between 2000 and 2015, the Industrial Minerals Association (IMA-Europe) launched a dust monitoring program (DMP), collecting over 28,000 personal measurements of respirable dust and quartz in 23 European countries, leading to the creation of a database.…”
Section: Introductionmentioning
confidence: 99%